2023
DOI: 10.1038/s41597-023-02113-2
|View full text |Cite
|
Sign up to set email alerts
|

Introduced and invasive alien species of Antarctica and the Southern Ocean Islands

Abstract: Open data on biological invasions are particularly critical in regions that are co-governed and/or where multiple independent parties have responsibility for preventing and controlling invasive alien species. The Antarctic is one such region where, in spite of multiple examples of invasion policy and management success, open, centralised data are not yet available. This dataset provides current and comprehensive information available on the identity, localities, establishment, eradication status, dates of intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Antarctica has long been considered a geographically isolated continent [1]. Consequently, the introduction of any organism has the potential to disrupt the existing biota [2][3][4]. Even microorganisms responsible for causing infections in humans face substantial barriers in reaching the continent [5].…”
Section: Introductionmentioning
confidence: 99%
“…Antarctica has long been considered a geographically isolated continent [1]. Consequently, the introduction of any organism has the potential to disrupt the existing biota [2][3][4]. Even microorganisms responsible for causing infections in humans face substantial barriers in reaching the continent [5].…”
Section: Introductionmentioning
confidence: 99%
“…Coccinella undecimpunctata is established in North America (Smyth et al, 2013 ), Australia (Pope, 1988 ) and New Zealand (Galbreath & Cameron, 2015 ). It has not been recorded in the natural environment on South Georgia or elsewhere in the sub‐Antarctic (Leihy et al, 2023 ), although Houghton et al ( 2016 ) note that it has been found in association with cargo on Antarctic logistics vessels. Here we provide the first report of the presence of the Eurasian ladybird, C. undecimpunctata Linnaeus (1758) (Coleoptera: Coccinellidae) on South Georgia.…”
Section: Introductionmentioning
confidence: 99%